“Smart cities” and their vulnerability - Oldřich Krulík; Jan Kolouch; Marek Pačmag (Acta Polytechnica CTU Proceedings, 2024)
In most discussions, “smart cities” are perceived as a largely positive phenomenon that improves the safety but above all the comfort of its inhabitants. The present paper constructively and critically analyses the approach of de facto unregulated development of “smart cities” with emphasis on the risks associated with this phenomenon. Examples from recent years, not only in the context of developments in Ukraine, show that modern, technological solutions, i.e. e-Government tools, can become a target or even a tool of variously motivated attackers (criminal groups, foreign powers). A “smart” city is often potentially more vulnerable than agglomerations managed more traditionally. This paper aims to demonstrate the possible risks through case studies and determine whether there are more comprehensive theoretical approaches to the subject.